Domestic Violence and the Newsprint Media: A Critical Discourse Analysis of Three Canadian Newspapers in a Covid-19 Context - Griffith, Brianna (My University, 2022)
This paper seeks to explore the way the print news media reported on issues related to domestic violence (DV) in the Greater Toronto/Hamilton Ontario area in the context of Covid-19 from March 2020 to March 2021. Specifically, I drew on three newspapers to include the Hamilton Spectator, the Toronto Star, and the Globe and Mail. This research is primarily concerned with the discourses that emerged about gender-based violence in the newsprint media during a time when people were required to stay in their homes and when access to community-based services that support women experiencing DV became increasing challenging. Using a Critical Discourse Analysis (CDA) that was grounded in a feminist theoretical framework, three themes emerged as particularly dominant. These included: a) the media’s use of “victim” and “survivor” discourses, b) women’s experiences of DV and access to resources, and c) public health discourses that centered on responses to DV in light of Covid-19. This paper concluded that reinforcement of dominant narratives about the socio political and gendered landscape in which DV is reported on via newsprint media sources, depict DV as an individual rather than structural issue that shifts the blame away from historical and current day social, economic, and political forces that create the conditions in which DV occurs. Importantly, the newsprint media promote a homogenous definition of ‘woman’ thus elevating dominant DV discourses that tend to centre the experiences of white, heterosexual women and that result in silencing the voices of gender diverse and racialized women. Consequently, my research suggests that there is an ongoing need to build on existing feminist literature to critically examine DV as a systemic issue that requires a response that is inclusive of the diversity of women who experience DV, the needs for services to support a diversity of women, and to do so in ways that move away from individual solutions toward shifts in practice and policy.
Keywords: Domestic Violence; Power; Feminist Theory; Newsprint Media